B7-H3 in glioblastoma and beyond: significance and therapeutic strategies - Babič, Davor; Jovčevska, Ivana; Zottel, Alja (Frontiers in Immunology, 2024)
Cancer has emerged as the second most prevalent disease and the leading cause of death, claiming the lives of 10 million individuals each year. The predominant varieties of cancer encompass breast, lung, colon, rectal, and prostate cancers. Among the more aggressive malignancies is glioblastoma, categorized as WHO stage 4 brain cancer. Following diagnosis, the typical life expectancy ranges from 12 to 15 months, as current established treatments like surgical intervention, radiotherapy, and chemotherapy using temozolomide exhibit limited effectiveness. Beyond conventional approaches, the exploration of immunotherapy for glioblastoma treatment is underway. A methodology involves CAR-T cells, monoclonal antibodies, ADCC and nanobodies sourced from camelids. Immunotherapy’s recent focal point is the cellular ligand B7-H3, notably abundant in tumor cells while either scarce or absent in normal ones. Its expression elevates with cancer progression and serves as a promising prognostic marker. In this article, we delve into the essence of B7-H3, elucidating its function and involvement in signaling pathways. We delineate the receptors it binds to and its significance in glioblastoma and other cancer types. Lastly, we examine its role in immunotherapy and the utilization of nanobodies in this domain.